2016
DOI: 10.1161/circulationaha.115.016801
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Abdominal Fatness, and Heart Failure Incidence and Mortality

Abstract: T he prevalence of overweight and obesity has increased rapidly over the last decades in all areas of the world. 1 This has raised serious public health concerns owing to the association between overweight and obesity and the increased risk of a wide range of chronic diseases, including cardiovascular diseases, type 2 diabetes mellitus, total mortality, and several types of cancer. 2-4 Clinical Perspective on p 649Heart failure is a major public concern. Heart failure affected ≈5 million Americans in 2005, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(127 citation statements)
references
References 64 publications
7
115
0
5
Order By: Relevance
“…This could indicate that part of the association between adiposity and atrial fibrillation may be mediated by heart failure. This is consistent with our previous finding of an increased risk of heart failure related to both general and abdominal adiposity [7] and with the increased risk of atrial fibrillation among patients with heart failure [53]. Although the heterogeneity between studies was high, this appeared to be largely due to different effect sizes between studies, rather than differences in the direction of the association, as all but one study found a positive association.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This could indicate that part of the association between adiposity and atrial fibrillation may be mediated by heart failure. This is consistent with our previous finding of an increased risk of heart failure related to both general and abdominal adiposity [7] and with the increased risk of atrial fibrillation among patients with heart failure [53]. Although the heterogeneity between studies was high, this appeared to be largely due to different effect sizes between studies, rather than differences in the direction of the association, as all but one study found a positive association.…”
Section: Discussionsupporting
confidence: 91%
“…Adiposity is associated with increased risk of hypertension [2], insulin resistance [69], diabetes [70], obstructive sleep apnea [71], coronary heart disease [72], and heart failure [7], which are established risk factors for atrial fibrillation [53, 73, 74]. Adiposity is associated with increased risk of left ventricular hypertrophy [7577] and left atrial size [78, 79], and the latter may be due to hypertension, volume overload, left ventricular diastolic abnormalities, autonomic dysfunction and enhanced neurohormonal activation [80, 81].…”
Section: Discussionmentioning
confidence: 99%
“…( J Am Heart Assoc. 2016;5:e003921 doi: 10.1161/JAHA.116.003921) Key Words: coronary heart disease • epidemiology • heart failure • obesity • stroke O besity is a common risk factor for several subtypes of cardiovascular disease (CVD), including coronary heart disease (CHD), stroke, and heart failure (HF) [1][2][3][4] ; however, increasing evidence suggests that obesity leads to various subtypes of CVD through multiple distinct pathways. Some traditional risk factors, including hypertension, diabetes mellitus, and dyslipidemia, are established as mediators between obesity and atherosclerotic vascular disease.…”
mentioning
confidence: 99%
“…Next, we assessed the relationships between the top 15 features associated with heart failure from the gradient boosting machine model and incident heart failure by using Cox proportional hazards regression in 2 sets of models: (1) adjusting for age and sex; and (2) additionally adjusting for body mass index, systolic and diastolic blood pressure, antihypertensive treatment, alcohol consumption, diabetes mellitus, smoking status, prevalent chronic renal failure, and prevalent coronary heart disease, all of which are established risk factors for heart failure 7, 8, 9, 10, 11. Continuous variables were entered as restricted cubic splines to account for any nonlinear associations.…”
Section: Methodsmentioning
confidence: 99%